Analisis Persepsi Konsumen dan Citra Merek Belanja Online di Floralclothing - Priscilla, Cherise; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Floralclothing is an online shop that was founded in 2019 and operates in the world of fashion. This research aims to determine consumer perceptions of product quality, style and values ​​that have been associated with Floralclothing in the context of online shopping. This research was conducted using a qualitative research approach. The theory used in this research is the S-O-R Theory (Stimulus, Organism, Response). The results of this research show that the use of e-commerce platforms is accompanied by responses, assessments or reviews, both positive and negative, from consumers as product buyers which will then stimulate other consumers' decisions. If the communicant or consumer can understand the stimulus or message, then accept and respond to it, then there is an intention in making a decision to purchase Floralclothing products so that this will indirectly make the consumer's perception positive and the Floralclothing brand image will increase. Communication in marketing is carried out by Floralclothing to establish a harmonious relationship with consumers so that Floralclothing 's brand image also increases and consumer perceptions become positive. Communication is very important to be applied by companies or online businesses because of positive communication to customers, consumer perceptions and improving brand image and customer loyalty. Floralclothing merupakan sebuah online shop yang berdiri sejak tahun 2019 dan bergerak di dunia fashion. Penelitian ini bertujuan untuk mengetahui persepsi konsumen terhadap kualitas produk, gaya, dan nilai-nilai yang telah diasosiasikan Floralclothing dalam konteks belanja online. Penelitian ini dilakukan dengan menggunakan pendekatan penelitian kualitatif. Adapun teori yg digunakan dalam penelitian ini adalah Teori S-O-R (Stimulus, Organism, Response). Hasil penelitian ini menunjukkan bahwa penggunaan platform e-commerce berdampingan dengan adanya tanggapan, penilaian atau review baik itu positif maupun negatif dari konsumen selaku pembeli produk yang kemudian akan menstimuli keputusan konsumen lainnya. Apabila komunikan atau konsumen dapat memahami stimulus atau pesan tersebut, kemudian menerima dan meresponnya, maka ada niat dalam mengambil keputusan pembelian produk Floralclothing sehingga secara tidak langsung akan membuat persepsi konsumen menjadi positif serta citra merek Floralclothing meningkat. Komunikasi begitu penting diterapkan oleh perusahaan atau pelaku bisnis online karena adanya komunikasi positif kepada kosnumen, persepsi konsumen dan meningkatkan citra merek (brand image) serta loyalitas pelanggan.